THE IMPLEMENTATION OF SERVICE QUALITY METHODS - Elwisam; Suadi Sapta Putra; Rahayu Lestari; Kumba Digdowiseiso; Abdul Hafaz Ngah (RADJA PUBLIKA, 2024)
This study examines the literature on the use of the Service Quality Method to improve the quality of service in a variety of industries. The research background emphasizes the importance of customer service as the key to company success in today's increasingly competitive business environment. These methods, particularly models like SERVQUAL, provide a comprehensive framework for assessing customer satisfaction across the dimensions of dependability, responsiveness, accuracy, care, and physical appearance. However, there are some flaws, such as limitations in measuring subjective dimensions, the difficulty of measuring emotional aspects, and rapid changes in consumer behavior. Some of these weaknesses have been addressed through the use of technology, such as big data analysis and artificial intelligence. According to literature analysis, technology allows for a better understanding of customer behavior, increased service personalization, and more effective response to market dynamics. Despite the significant benefits, the use of technology raises concerns about data security and privacy. In conclusion, this literature review demonstrates that the Service Quality Method contributes significantly to service quality management, but companies must consider the limitations and challenges of technology when implementing it. More work is required to keep this method relevant in the face of ever-changing consumer behavior and technological advancements.